Fidel Castro Ruz on language education. A guide for educational innovation - Enríquez O´Farrill, Isora Justina (Transformación, 2024)
Objectives: Language education has been part of the socio-educational and cultural projects of the Cuban Revolution, marked by Fidel Castro Ruz’s thought, as it has been reflected in many of his speeches. This paper aims at compiling the Fidel Castro Ruz’s main ideas on foreign language learning pronounced in his speeches from 1959 to 2006. The selection and discussion of those quotations become guidelines for the present process of curriculum renewal, so that teachers of English and trainees enrich their understanding of the concepts behind education. Methods: The leading methods have been document study, analysis-synthesis, induction- deduction, from a historical and logical perspective to systematize the pedagogical ideas identified in Fidel´s speeches that have become guidelines for the present process of curriculum renewal. Results: The selection and systematization of quotations by Fidel Castro Ruz about the importance of language education, particularly English language education. Conclusions: Fidel Castro rug’s reflections about the importance and need of language education have contributed to substantiate the renovation of the theoretic-pedagogical framework for English language education and the innovations needed in the present process of curriculum renewal.